Modelling of fire-suppressant injection into engine nacelle for various flight regimes - Mohamed Arif Mohamed (2023)
In this study, the injection of Halon 1301, an effective fire-suppressing agent, into a helicopter engine nacelle is modelled to provide insights into dispersion behaviour alongside complex flow physics. The injection velocity as well as the mass flow rate were retrieved via a 1-D pipe model to simulate nitrogen-pressurized flow of Halon 1301 in a four-branch pipe system. The Discrete Phase Model in ANSYS Fluent was then used to model the injection of Halon 1301 into an engine nacelle. To simulate engine operation conditions in forward flight and hover regime, external boundary conditions were prescribed to the pressure inlets in the nacelle. When Halon 1301 is injected into the engine bay via the first pair of injection points, the droplets immediately reach their boiling point of 215 K. This resulted in an explosive-dispersion behaviour with a cone angle in the range of 80°–90°. As the agent evaporates, the engine cools and another pair of injection points located at the rear of the engine is subsequently activated, helping to cool the engine further. The two flight regimes considered, namely, hover and forward flight, showed contrast in flow dynamics which affected the cooling of the engine as well as the spray dynamics. In particular, the forward flight case showed more recirculation zones compared to the hover case. The volume concentrations of Halon 1301 were plotted for 11 probe points within the nacelle, and it was observed that two locations showed traces of low concentration levels.